2020
DOI: 10.20944/preprints202002.0071.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drug and Vaccine Design against Novel Coronavirus (2019-nCoV) Spike Protein through Computational Approach

Abstract: The recent outbreak of the new virus in Wuhan city, China from the sea food market has led to the identification of a new strain called the corona virus and named as novel corona virus (2019-nCoV) belonging to Coronaviridae family. This has created major havoc and concern due to the mortality of 250 persons and affecting more than 10,000 people. This virus causes sudden fever, pneumonia and also kidney failure. In this study a computational approach is proposed for drug and vaccine design. The spike protein se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
0
22
0
2
Order By: Relevance
“…In the vaccine design, B-cell epitope VLLPLVSSQCVNLTTRTQLPPAYTN was found to have the highest antigenicity. FVFLVLLPL of MHC class-I allele and FVFLVLLPL of MHC class-II allele were identified as best peptides based on several alleles and antigenicity scores [139]. Therefore, identifies natural inhibitors and putative antigenic epitopes might be useful as effective drug and vaccine candidates for the eradication of novel coronavirus.…”
Section: Drug and Vaccine Design Against Novel Coronavirus Spike Proteinmentioning
confidence: 99%
“…In the vaccine design, B-cell epitope VLLPLVSSQCVNLTTRTQLPPAYTN was found to have the highest antigenicity. FVFLVLLPL of MHC class-I allele and FVFLVLLPL of MHC class-II allele were identified as best peptides based on several alleles and antigenicity scores [139]. Therefore, identifies natural inhibitors and putative antigenic epitopes might be useful as effective drug and vaccine candidates for the eradication of novel coronavirus.…”
Section: Drug and Vaccine Design Against Novel Coronavirus Spike Proteinmentioning
confidence: 99%
“…According to his estimate, it takes eight months to a year for the SARS-CoV-2 vaccine to be rigorously tested before it is ready for public use [67]. It is also imperative to analyze the rate of SARS-CoV-2 genome evolution and to determine peptide vaccine targets [68]. There are eight CD4 T-cell epitopes with high binding affinity within S, E, M, and N proteins that are generally restricted by the human leukocyte antigen (HLA)-DR alleles found in Asian and Asian-pacific populations [69].…”
Section: Sars-cov-2 Vaccine Under Developmentmentioning
confidence: 99%
“…Recently, few studies have been reported on epitope identification for SARS-CoV-2 vaccine construct using immunoinformatics approach [29][30][31][32]. However, these in silico analysis are majorly on spike protein and most importantly, regardless of the importance of RBD region of spike protein in the pathogenesis of SARS-CoV-2 virus, none have focused on identification of conserved epitopes spanning the antigenic RBD region.…”
Section: Introductionmentioning
confidence: 99%